2014
DOI: 10.1016/j.jfma.2014.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Acute renal injury after thoracic endovascular aortic repair of Stanford type B aortic dissection: Incidence, risk factors, and prognosis

Abstract: A significant rate of AKI was observed following TEVAR and was associated with an increase in 30-day and 1-year mortality. Malperfusion complications were identified as an independent predictor of AKI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 29 publications
1
20
0
2
Order By: Relevance
“…Patients in stages 2 and 3 had significant higher rates of in-hospital mortality and major adverse events. Similar incidence of AKI was found in the study by Zhu et al, 23 which identified AKI in 48 (30.8%) of 156 TEVAR for TBAD patients according to RIFLE (risk, injury, failure, lose and end-stage renal disease) classification, with 7 (14.5%) patients requiring continuous RRT. Other previous studies, however, have suggested the rates of AKI after endovascular repair varying from 1.5% to 34%.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Patients in stages 2 and 3 had significant higher rates of in-hospital mortality and major adverse events. Similar incidence of AKI was found in the study by Zhu et al, 23 which identified AKI in 48 (30.8%) of 156 TEVAR for TBAD patients according to RIFLE (risk, injury, failure, lose and end-stage renal disease) classification, with 7 (14.5%) patients requiring continuous RRT. Other previous studies, however, have suggested the rates of AKI after endovascular repair varying from 1.5% to 34%.…”
Section: Discussionsupporting
confidence: 85%
“… 5 7 The rates of postprocedure AKI after endovascular repair for thoracic or abdominal aortic aneurysm alone were relatively low ranging from 2% to 17%, 26 29 when compared with TEVAR for TBAD which ranged from 27.5% to 30.8%. 23 The differences in pathophysiology between aortic dissection and aneurysm may also be factor to consider, including hemodynamic changes by the TL/FL, the dissection flap, the load of contrast agent and the controlled BP depressurization during stent deployment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Retrospective studies have been undertaken to assess the prevalence and the clinical and biochemical features of AKI following clindamycin treatment (6)(7)(8). AKI related to the administration of clindamycin is generally associated with oligoanuria, the same as in our patient.…”
Section: Discussionmentioning
confidence: 87%
“…The incidence of acute kidney injury (AKI) after TEVAR has been reported to be 1% to 34% [ 4 ]. This relatively common complication of TEVAR is associated with prolonged hospital stays and increased risk of mortality [ 5 7 ]. The goal of this clinical research was to investigate the risk factors and impact of AKI after TEVAR.…”
Section: Introductionmentioning
confidence: 99%